The Latvian Translation Scene at the Beginning of the 20th Century - Andrejs Veisbergs (Baltic Journal of English Language, Literature and Culture)
The first decade of the 20th century was a period of huge advances and expansion in the Latvian translation scene. New, contemporary authors’ works became available to Latvian readers. The Latvian readership was consciously being integrated into general European literary trends. It was also a heyday of periodicals that published numerous translations, including numerous novels. There are countless parallel translations even reaching double digits. Translations included various genres and the traditional Latvian interest in plays was obvious. German was gradually losing its dominant positions as both a source and intermediate language, Russian was advancing. This period also saw a change of generations among translators, and with the new generation women became visible in translation scene. Practically all Latvian writers were also active translators. The translation method changed from localisation to a fidelity mode with a tendency towards foreignisation. Frequently translations now had prefaces and explanations by the translators. Translated literature now ranged from serious classical works to modern ones and from pulp literature to high quality creations. The quality of translations was also very varied. T he expansion of translation and the cultivation of new domains went hand in hand with the development of the Latvian language itself.